SOCIOCULTURAL FACTORS THAT INFLUENCE THE USE AND MEANING OF SLANG IN THE ENGLISH LANGUAGE - Kemalatdinova Jakhangul Polatbayevna; Alimova Gulnazkhon Yuldashaliyevna (Journals Park Publishing, 2023)
Slang is an informal language that reflects the attitudes, beliefs, and values of particular groups of people, and can be shaped by historical events, regional differences, social class, and the influence of popular culture. Understanding these factors can help us to better understand the use and meaning of slang, as well as the social and cultural contexts in which it is used. While slang can be a fun and expressive way to communicate, it's important to be aware of its impact and to use it in a respectful and inclusive way.
Keywords: slang, social class, cultural context, socioeconomic status, ethnicity, entertainment, political and social issues, technology.